Bridging the gap: cancer scientific equity, global child health, and distribution of CAR T-cell therapy clinical trials in childhood cancer - Montoya-Quintero, Kevin Fernando; Galván-Barrios, Johana; Martinez-Guevara, Darly; Dueñas, Diana; Montenegro, John; Liscano, Yamil (Frontiers in Pediatrics, 2025)
Chimeric antigen receptor (CAR) T-cell therapy has transformed the treatment land-scape for childhood cancer. However, its global distribution remains unequal, with limited access in regions bearing a high burden of disease. This situation raises critical concerns about scientific equity in pediatric oncology research worldwide. To date, no study has systematically examined the scientific coherence between child health needs, global health indicators, and the frequency of CAR T-cell therapy clinical trials for childhood cancer. This omission represents a significant gap in the literature, with im-plications for global health equity and cancer research prioritization. A mixed-method analysis was conducted using global health metrics, child cancer indicators, and data from the Global Observatory on Health Research and Development. A total of 414 CAR T-cell therapy clinical trial participations across 30 countries were identified, with a heavy concentration in China (n = 161) and the United States (n = 84). High-income countries represented 73.3% of those participating. Multiple linear regression identified only one significant predictor for clinical trials participation: youth mortality (<15 years) (Coef. = 161.53; p = 0.045). The Lasso model revealed key predictors such as deaths due to alcohol use (Coef. = 29.99) and obesity (Coef. = 9.62) in children aged 5–14. Findings reveal a structural misalignment between childhood cancer disease burden and research activity in advanced therapies. Clinical trials are concentrated in countries with stronger scientific infrastructure rather than those with the greatest health needs, reinforcing cancer scientific inequities in the production and distribution of biomedical knowledge.